Impact of deep brain stimulation on urogenital function in Parkinson’s disease: a systematic review and meta-analysis - Gao, Long; Wang, Meng; Zhou, Mengdi; Yin, Wenjuan; Cao, Xiaoming (Frontiers in Neurology, 2024)
Objectives Deep Brain Stimulation (DBS) effectively treats Parkinson’s motor symptoms, but its effects on the urogenital system are debated. Methods A research was conducted in PubMed, Embase, Cochrane Library, Web of Science, and Scopus until February 27, 2024. We primarily focused on DBS’s impact on Parkinson’s patients’ Urine storage function, voiding function, sexual function, and quality of life. Results Our meta-analysis included 14 studies. The main results showed that DBS resulted in fewer instances of urinary urgency (OR = 1.85, 95% CI: 1.26 to 2.70, p = 0.002) and increased maximum bladder capacity (MD = −66.10, 95% CI: −119.37 to −12.82, p = 0.02) in terms of urinary storage function. However, there were no significant differences in first desire to void and strong desire to void. In terms of voiding function, DBS showed significant improvements in maximum flow rate (MD = −0.64, 95% CI: −1.23 to −0.05, p = 0.03), post-void residual (MD = −6.79, 95% CI: 4.54 to 9.05, P < 0.00001) and detrusor pressure during maximum flow (MD = −1.37, 95% CI: −2.73 to −0.02, p = 0.05). Additionally, there was no significant difference in sexual function between the two groups (MD = −1.41, 95% CI: −12.40 to 9.57, p = 0.80). Conclusion DBS has demonstrated a certain degree of efficacy in ameliorating urinary storage and voiding function in patients with Parkinson’s disease. However, certain urodynamic parameters or scores do not demonstrate any statistically significant disparities. Furthermore, DBS has no significant impact on erectile function in male Parkinson’s patients. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023476661, identifier CRD42023476661.